Performance Optimization Through The Dimension Of Job Satisfaction - Achmad Yudha; Roni Kambara; Dibyantoro Dibyantoro (Cakrawala Repositori IMWI, 2023)
This study attempts to explore more deeply the correlation between the effect of job involvement, digital work design, and IPC organizational culture on the main context of employee performance using job satisfaction as the main mediator. This method uses a quantitative approach with data collection through questionnaires to measure employee perceptions with an interval scale of 1-100 to organic employees, the sampling technique uses simple random sampling and data processing using the SEM-PLS instrument. Research findings describe a positive correlation between job involvement on direct performance as well as engagement, and IPC organizational culture on satisfaction. While digital work design does not affect satisfaction and satisfaction is found to not affect the performance context. This study was only conducted on tinplate manufacturing employees in the short term, future studies need to explore further using a longitudinal design approach with a more complex research locus.